2015
DOI: 10.1002/14651858.cd009279.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing recurrent urinary tract infection during pregnancy

Abstract: Background Recurrent urinary tract infections (RUTI) are common in women who are pregnant and may cause serious adverse pregnancy outcomes for both mother and child including preterm birth and small-for-gestational-age babies. Interventions used to prevent RUTI in women who are pregnant can be pharmacological (antibiotics) or non-pharmacological (cranberry products, acupuncture, probiotics and behavioural modifications). So far little is known about the best way to prevent RUTI in pregnant women. Objectives To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 48 publications
2
19
0
11
Order By: Relevance
“…2,120,121 Daily prophylactic therapy with 50 to 100 mg of nitrofurantoin should also be considered. Although there is limited highquality evidence that antimicrobial prophylaxis decreases bacteriuria in pregnancy, 122,123 this is a well-established therapy in nonpregnant patients. 124 Postcoital prophylaxis can also be considered.…”
Section: Follow-up and Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,120,121 Daily prophylactic therapy with 50 to 100 mg of nitrofurantoin should also be considered. Although there is limited highquality evidence that antimicrobial prophylaxis decreases bacteriuria in pregnancy, 122,123 this is a well-established therapy in nonpregnant patients. 124 Postcoital prophylaxis can also be considered.…”
Section: Follow-up and Preventionmentioning
confidence: 99%
“…35 Follow-up, including periodic screening for recurrent bacteriuria and consideration of daily antimicrobial prophylactic therapy, is also recommended after treatment. [122][123][124][125] …”
Section: Lower Urinary Tract Infections (Cystitis)mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to sUTI, which is resolved in most cases by treatment (Hooton, 2003;Gupta et al, 2011), therapy is not routine for ABU (Nicolle et al, 2005;Nicolle, 2006). While treatment can halt the progression of bacteriuria and reduce the incidence of infection (Schneeberger et al, 2012), patients infected with E. coli experience recolonization with the same or similar organism at surprisingly high rates (Dalal et al, 2009). These data reveal the difficulty in achieving bacteriological cure for ABU and imply that bacteriuria involves frequent recolonization of the host.…”
Section: What Factors Influence the Progression Of Bacteriuria?mentioning
confidence: 99%
“…5,6 However, similar to ours, several studies have suggested that the risk of early delivery among women with a UTI persists despite treatment. 11,25,26 We showed that women were at elevated risk of PTB regardless of treatment when the UTI was diagnosed at an inpatient or outpatient visit within 6 months of delivery. This suggests that treatment may not adequately halt the inflammatory cascade leading to PTB, and that infection early in pregnancy is still associated with early parturition months later.…”
Section: Discussionmentioning
confidence: 93%